﻿Systematic reinstatement of the Sumatra endemic species Mangifera sumatrana Miq. (Anacardiaceae) - Fitmawati Fitmawati; Erwina Juliantari; Mega Silvia (PhytoKeys, 2022)
Mangifera sumatrana Miq. is an endemic species from Sumatra. The taxonomic status of M. sumatrana remains unclear and is currently treated as a synonym of M. laurina. The present study employed morphological and palynological characters and molecular analyses to address the delimitation between the two species. Pollen observations were carried out with a Scanning Electron Microscope (SEM). Phylogenetic relationships were investigated using the ITS and the trnl-F intergenic spacer markers. M. sumatrana differs from M. laurina by having pyramidal panicles with a low density of pale yellow flowers pale, sepals 3–3.5 × 1.7–2 mm, fruit roundish to flattened with pale yellow pulp, a rough fibre texture, and pollen with a prolate spheroidal shape. The MP phylogenetic tree showed a divergent boundary between the two species suggesting that M. sumatrana could be an independent species, not a variety of M. laurina. The present study supports the view that these two taxa can be treated as different species.